Músicos de Sabará: a prática musical religiosa a serviço da Câmara (1749-1822) - Daniela Miranda (2002)
This dissertation presents an analysis of the musical activity performed close to the Senate of Vila Real de Sabará, during the period between 1749 and 1822.The musicians as other representatives of the arts and of the occupations (carpenter, tailor, blacksmith, shoemaker, etc) of the village were regularly requested to act in the events promoted by the Chamber. Thus, the commemorations became the main point of support of the music performance, and through its registrations it has been possible to recover important information regarding the demand for the music, the fulfilled contracts, the executed services, and the values received by the musical service.The dissertation also discusses the meaning of the festive practices and the interests involved in the organization and promotion of those celebrations, and presents the instrumental and vocal structure of the groups that used to act in those celebrations based on pertinent bibliography regarding the theme, and the inventories and testaments of the regional musicians.